Semi-perfect Sets in Topological Spaces (Journal of Humanitarian and Applied Sciences, 2023)
In this paper, we introduce a new concept called semi-perfect sets in topological spaces. We define semi-isolated points and semi-perfect sets. Further, some interesting results and properties of these concepts are investigated.
Keywords: Semi-perfect set; Semi-isolated point; Semi-closed set; Semi-open set.